Band structure and spin texture of 2D materials for valleytronics: insights from spin and angle-resolved photoemission spectroscopy - F Bussolotti; T D Maddumapatabandi; K E J Goh (Materials for Quantum Technology, 2023)
In this review, we present a perspective on the use of angle-resolved photoemission spectroscopy (ARPES) and spin-resolved ARPES (SARPES) for the study of the electronic properties of semiconducting transition metal dichalcogenides (TMDCs), a prime example of two-dimensional (2D) materials for valleytronics applications. In the introductory part, we briefly describe the structural and electronic properties of semiconducting TMDCs and the main valleytronics related physical effects. After a short presentation of theoretical methods utilized in the band structure and spin texture calculation of semiconducting TMDCs, we illustrate the basic principles and methodology of photoemission techniques and then provide a detailed survey on the electronic band structure studies of these materials. In particular, by selecting and comparing seminal results in the field, we highlight the critical role played by the sample preparation strategy on the amount and quality of information that can be extracted in the ARPES investigations of TMDCs. This is followed by a detailed discussion on the impact of interface potential landscape and doping on their electronic properties, considering the importance of their contact with metal electrode and/or dielectric substrate in determining the electrical transport in real devices’ architecture. Finally, we summarize key SARPES findings on the spin texture of TMDCs and conclude by pointing out current open issues and potential directions for future photoemission-based studies on these 2D systems.